2008
DOI: 10.1111/j.1365-2125.2008.03250.x
|View full text |Cite
|
Sign up to set email alerts
|

Lamotrigine does not prolong QTc in a thorough QT/QTc study in healthy subjects

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT • Drugs that inhibit the human cardiac delayed rectifier potassium current may lead to prolongation of the cardiac QT interval and are associated with a fatal, polymorphic, ventricular tachycardia known as torsades de pointes. • Lamotrigine is indicated in the treatment of epilepsy and the prevention of mood episodes in patients with bipolar disorder. • Lamotrigine inhibits the human cardiac delayed rectifier potassium current in vitro, and it has been hypothesized tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
72
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(88 citation statements)
references
References 31 publications
10
72
0
4
Order By: Relevance
“…However, some studies involving Caucasian subjects showed larger QTcF effects [15][16][17] . Therefore, further studies are required to determine ethnicity-specific effects, especially prospectively designed direct comparisons of moxifloxacininduced QT prolongation in Asians versus Caucasians.…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies involving Caucasian subjects showed larger QTcF effects [15][16][17] . Therefore, further studies are required to determine ethnicity-specific effects, especially prospectively designed direct comparisons of moxifloxacininduced QT prolongation in Asians versus Caucasians.…”
Section: Discussionmentioning
confidence: 99%
“…
In a thorough QT/QTc study of lamotrigine [1], healthy subjects received a single oral dose of moxifloxacin (400 mg) or placebo in crossover design, followed by a doseescalating regimen of lamotrigine (n = 76) over a 77 day period, or matched placebo (n = 76). Digital 12-lead electrocardiograms (ECGs) were recorded and ECG intervals measured manually by a central reader.
…”
mentioning
confidence: 99%
“…Digital 12-lead electrocardiograms (ECGs) were recorded and ECG intervals measured manually by a central reader. In a post hoc analysis, PR interval data were analysed using repeatedmeasures analysis of covariance (ANCOVA) separately for day 42 (lamotrigine 50 mg twice daily), day 63 (lamotrigine 150 mg twice daily) and day 77 (lamotrigine 200 mg twice daily) as previously described [1]. Point estimates and corresponding 90% confidence intervals (CIs) were calculated for the difference between each dose of lamotrigine and the corresponding placebo at each time point.…”
mentioning
confidence: 99%
“…In the anticonvulsant group, there were three cases of lamotrigine, which has been reported to have sodium channel-blocking effects [57,58]. There was only one case of VT/VF associated with valproic acid overdose and no cases of TdP; previous case reports suggest that valproate may cause QTc prolongation, possibly due to hypocalcemia [59,60].…”
Section: Discussionmentioning
confidence: 86%